2022
DOI: 10.1186/s12984-022-00980-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reorganization to improve dynamic balance control with error amplification feedback

Abstract: Background Error amplification (EA), virtually magnify task errors in visual feedback, is a potential neurocognitive approach to facilitate motor performance. With regional activities and inter-regional connectivity of electroencephalography (EEG), this study investigated underlying cortical mechanisms associated with improvement of postural balance using EA. Methods Eighteen healthy young participants maintained postural stability on a stabilomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…According to the cortical idling hypothesis, increases in alpha activity over the sensorimotor area are related to sluggish execution of movements ( Pfurtscheller et al, 1996 ). Analogous to visual occlusion in upright stance ( Goh et al, 2016 ), the intermittent visual feedback also brought about marked augmentation of the alpha power in the sensorimotor regions during stabilometer stance ( Figure 2B , middle), in relation to less visuospatial attention for postural tracking ( Chen et al, 2022 ). The EEG observation supported that visual reliance during stabilometer stance was downregulated by SV.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the cortical idling hypothesis, increases in alpha activity over the sensorimotor area are related to sluggish execution of movements ( Pfurtscheller et al, 1996 ). Analogous to visual occlusion in upright stance ( Goh et al, 2016 ), the intermittent visual feedback also brought about marked augmentation of the alpha power in the sensorimotor regions during stabilometer stance ( Figure 2B , middle), in relation to less visuospatial attention for postural tracking ( Chen et al, 2022 ). The EEG observation supported that visual reliance during stabilometer stance was downregulated by SV.…”
Section: Discussionmentioning
confidence: 95%
“…Previous researches showed that mid-frontal theta power is involved with the organization of goal-directed movements and postural balance maintenance ( Hulsdunker et al, 2015 ; Malcolm et al, 2021 ). When a subject was guided by visual feedback during stabilometer stance, the mid-frontal theta power was enhanced to elaborate worse outcomes even though the visualized errors were faked ( Chen et al, 2022 ). In this study, the smaller mid-frontal theta oscillation in the SV condition ( Figure 2B , top) implied that fewer error contexts were perceived by the older adults with intermittent blocking of visual feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased θ-connectivity and -power in the frontal and central areas are thought to be induced by errors that need to be controlled under uncertain circumstances (Cavanagh and Frank 2014), and to serve to facilitate sensory-motor processing for standing balance (Mierau et al . 2017; Chen et al 2022). Our findings support these notions and underline the importance of the θ-frequency band for standing balance.…”
Section: Discussionmentioning
confidence: 99%
“…As occurs in healthy young adults 63 , short-term training with visual EA has the potential to leverage the principle of neuroplasticity to expedite the achievement of postural training goals for healthy older adults. In practice, visual EA can be easily delivered via virtual reality (VR) technology, which can provide flexible manipulation of the postural error size within an immersive gaming environment.…”
Section: Discussionmentioning
confidence: 99%